2022
DOI: 10.2147/dmso.s360689
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Serum Ferritin Levels in Vietnamese Adults with Metabolic Syndrome

Abstract: Background Metabolic syndrome is one of the most common public health concerns in the 21st century. Several previous studies have shown an association between increased serum ferritin levels and other components of metabolic syndrome and the risk of metabolic syndrome. They conclude that ferritin can be viewed as a predictor of metabolic syndrome risk. This study investigates some main features of metabolic syndrome and the serum ferritin levels in a Vietnamese adult cohort with metabolic syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…18 Furthermore, in obese patients, considering the chronic inflammatory state, there are already high levels of ferritin regardless of the infection. 19 So we demonstrated that MonoAbs remain a viable therapeutic option to treat COVID-19 disease and its complications, especially in obese individuals. Although they were not vaccinated and had a very high risk of serious illness, the infection after therapy resolved without complications.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…18 Furthermore, in obese patients, considering the chronic inflammatory state, there are already high levels of ferritin regardless of the infection. 19 So we demonstrated that MonoAbs remain a viable therapeutic option to treat COVID-19 disease and its complications, especially in obese individuals. Although they were not vaccinated and had a very high risk of serious illness, the infection after therapy resolved without complications.…”
Section: Discussionmentioning
confidence: 89%
“… 18 Furthermore, in obese patients, considering the chronic inflammatory state, there are already high levels of ferritin regardless of the infection. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, serum ferritin (SF) is the most used clinically. Previous animal and epidemiological studies observed a significant association between excess SF storage and glucose metabolism disorders, [10][11][12] and others have found a positive association between ferritin and type 2 diabetes. 13,14 Then, some epidemiological studies have investigated the relationship between high SF concentrations and the incidence of gestational diabetes mellitus (GDM), but the results have been controversial.…”
Section: Introductionmentioning
confidence: 77%
“…24 Similar findings were noted by other studies. 25,26 In patients with cardiovascular risk, hyperferritinemia was found to be well-correlated with MetS. 27 Likewise, the study of Srivastav et al 28 found as association between increased ferritin levels and MetS in hospitalized patients.…”
Section: Discussionmentioning
confidence: 96%